Electrically switchable birefringent self-assembled nanocomposites: ferroelectric liquid crystal doped with the multiwall carbon nanotubes. Issue 9 (14th July 2020) - Shukla, Ravi K.; Chaudhary, Ashok; Bubnov, Alexej; Hamplova, V.; Raina, K. K.
ABSTRACT: Functional nanocomposites are designed via doping ferroelectric liquid crystal (FLC) matrix by 0.03wt% and 0.1wt% of functionalised multiwall carbon nanotubes (MWCNTs). Mesomorphic, optical, thermo-optic and electro-optic behaviour of resulting nanocomposites have been studied in the ~5μm thick cells. Effect of applied voltage on the mesomorphic and electro-optic behaviour of ferroelectric liquid crystal has been established. Interestingly, FLC material demonstrates electrically switchable birefringence colours viz. yellow, reddish, violet and green colour, under applied electric field at different temperatures. No considerable perturbation of FLC smectic order has been observed with doping of MWCNTs. However, the MWCNT doping strongly modifies the optical contrast, birefringence, transmission and contrast ratio of the FLC material. The most significant results are obtained for nanocomposite with 0.03wt% MWCNTs concentration. Doping by MWCNTs leads to the generation of new colours in the nanocomposite systems and also effectively reduce the driving voltage for the colour appearance. For the designed nanocomposites, a decrease in the spontaneous polarisation and fastening of the switching time has been detected. Such electrically switchable birefringent MWCNTs/FLC nanocomposites can be effectively utilised for practical applications in the field-sequential colour displays, FLC switches, optoelectronic and photonic devices. GRAPHICAL ABSTRACT: uf0001